Structural and biochemical basis for the difference in the helicase activity of two different constructs of SARS-CoV helicase - Adedeji, A. O.; Singh, K.; Sarafianos, S. G. (Cellular and Molecular Biology, 2012)
The non-structural protein 13 (nsp13) of Severe Acute Respiratory Syndrome Coronavirus (SARS-CoV) is a helicase that separates double-stranded RNA or DNA with a 5’-3’ polarity, using the energy of nucleotide hydrolysis. We have previously determined the minimal mechanism of helicase function by nsp13 where we demonstrated that the enzyme unwinds nucleic acid in discrete steps of 9.3 base-pairs each with a catalytic rate of 30 steps per second. In that study we used different constructs of nsp13 (GST and H6 constructs). GST-nsp13 showed much more efficient nucleic acid unwinding than the H6-tagged counterpart. At 0.1 second, more than 50% of the ATP is hydrolyzed by GST-nsp13 compared to less than 5% ATP hydrolysis by H6-nsp13. Interestingly, the two constructs have the same binding affinity for nucleic acids. We, therefore propose that the difference in the catalytic efficiency of these two constructs is due to the interference of ATP binding by the histidine tag at the amino-terminus of nsp13.